Rancang Bangun Aplikasi M–Commerce Berbasis Android untuk Pemesanan Jamu Lokal pada Kelompok Tani Prima Mandiri di Timor Tengah Utara Menggunakan Metode Waterfall - Yulsiani Sanam; Yoseph P.K Kelen; Krisantus J. Tey Seran; Leonard Peter Gelu (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2024)
The Prima Mandiri Farmers Group is a business that operates in the field of selling local herbal medicine, including noni herbal medicine, ginger herbal medicine, soursop herbal medicine, white turmeric herbal medicine and ginger herbal medicine. However, based on the results of observations and interviews with business owners, it was stated that the marketing and sales system used by the Prima Mandiri Farmers Group is currently still done manually, that is, buyers must come directly to the business premises to see the various kinds of products available. Of course, with this sales system it will take up consumers' time to obtain information easily and accurately. So, an Android-based application will be designed to help sellers promote products and make it easier for customers to order local herbal medicine based on Android. This M-Commerce application is named Jamlok Shop (Local Jamu Shop). The method used in building this application is the waterfall method, the name of this model is actually